Body composition and its association with physical performance, quality of life, and clinical indictors in Charcot-Marie-Tooth disease: a pilot study. Issue 4 (13th February 2019) - Hackett, Daniel; Roberts-Clarke, Daniel; Jain, Nidhi; Mavros, Yorgi; Wilson, Guy C.; Halaki, Mark; Burns, Joshua; Nicholson, Garth; Fiatarone Singh, Maria; Fornusek, Che
Abstract: Aim: To investigate whether the amount and distribution of lean body mass and fat mass is associated with disease severity in adults with Charcot-Marie Tooth. Methods: Ten participants (age 46 ± 13 y, height 1.7 ± 0.1 m, and body mass 77 ± 17 kg) with Charcot-Marie Tooth disease were involved in this study. Participants were evaluated for quality of life, falls efficacy, balance, mobility, muscle strength, and power. Body composition was measured using dual energy x-ray absorptiometry. Statistical analyses were conducted on subsets of all participants. Results: Better static balance was associated with higher lean body mass of the lower leg ( r  = 0.73, p  = 0.03), while superior leg press strength and power was associated with greater lean body mass of the leg and lower leg ( r  ≥ 0.80, p  ≤ 0.01). Faster habitual walking speed and enhanced quality of life was associated with lower fat mass of several regions. Conclusion: Our study seems to suggest that assessing of body composition could assist with monitoring of disease progression in people with Charcot-Marie Tooth; however these findings need to be substantiated in a larger cohort. Implications for Rehabilitation: Higher lean body mass and lower fat mass of the legs is associated with better physical performances in people with Charcot-Marie-Tooth disease. Lower fat mass is related to greater quality of life and reduced clinical symptoms in people with Charcot-Marie-Tooth disease. Optimising favorable body composition profiles (higher lean body mass and lower fat mass) in people with Charcot-Marie-Tooth disease may be highly clinically relevant. Trial registration: Australian New Zealand Clinical Trials Registry identifier: ACTRN12614000173695.